2011
DOI: 10.1186/1757-7241-19-22
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life in trauma patients. Data from a one-year follow up study compared with the general population

Abstract: BackgroundTrauma patients have impaired health-related quality of life (HRQOL) after trauma. The aim of the study was to assess HRQOL during the first year after trauma and hospital stay in trauma patients admitted to an intensive-care unit (ICU) for >24 hours compared with non-ICU trauma patients and the general population, and to identify predictors of HRQOL.MethodsA prospective one-year follow-up study of 242 trauma patients received by the trauma team of a trauma referral centre in Norway was performed. HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
51
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 55 publications
7
51
0
3
Order By: Relevance
“…Health-related quality of life following trauma has been shown to be predicted by optimism and low levels of depression and post-traumatic stress. 13 Schiller et al interviewed patients following hip fracture who described seeking support, moving more and preserving perspective as the fundamental factors in improving outcome, 26 whereas other studies reported that psychological health was considered by patients as an important marker of recovery. 27,28 Although we did not specifically target questions to determine quality of life factors or personality traits, interestingly, in this population, those discharged home commonly reported that family support and their own strength of mind and determination were the major factors in achieving their goals, whereas those discharged to in-patient rehabilitation seemed to focus on the importance of others in their recovery, often claiming that it was the rehabilitation staff who were the reason for their positive outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health-related quality of life following trauma has been shown to be predicted by optimism and low levels of depression and post-traumatic stress. 13 Schiller et al interviewed patients following hip fracture who described seeking support, moving more and preserving perspective as the fundamental factors in improving outcome, 26 whereas other studies reported that psychological health was considered by patients as an important marker of recovery. 27,28 Although we did not specifically target questions to determine quality of life factors or personality traits, interestingly, in this population, those discharged home commonly reported that family support and their own strength of mind and determination were the major factors in achieving their goals, whereas those discharged to in-patient rehabilitation seemed to focus on the importance of others in their recovery, often claiming that it was the rehabilitation staff who were the reason for their positive outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies report that factors such as optimism and low post-traumatic stress lead to improved quality of life following trauma, 13 with personality traits such as an internal locus of control also being shown to contribute to positive outcomes after various fracture types. 14,15 The factors that patients' believe most assisted in their recovery were investigated in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…3,10,11 Patients in a trauma and burns ICU (TBICU) are at similar risk for these complications, 3,10,12 which may contribute to the body structure and function impairments, activity limitations, participation restrictions, and decreased quality of life seen in patients years after discharge from the TBICU. [13][14][15][16][17] Yet, no previous studies have investigated the safety, feasibility, or effectiveness of early mobilization in patients who are critically ill and who have sustained traumatic or burn injuries.…”
mentioning
confidence: 98%
“…Previous studies showed that the (HR)QOL of severely injured patients is lower than that of the general population. [2][3][4][5][6][7][8] This decrease in (HR)QOL seems to depend on both psychological complaints and physical limitations, but few studies measured these three parameters within the same study population.…”
Section: Introductionmentioning
confidence: 99%